The Application of Therapeutic Architecture Concepts in the Proposed Design of a Safe House in Tangerang City - Jennifer, Veronica; Asharhani, Imaniar Sofia; Ratnasari, Anisza (Talenta Publisher, 2024)
Violence against women and children is a serious issue in Indonesia, including in South Tangerang City, affecting various layers of society and having negative physical and psychological impacts. Proper and integrated intervention is a duty to protect and rehabilitate the victims. The design of a safe house is proposed as a solution for addressing cases of violence against women and children in Indonesia. This safe house is designed with a therapeutic architecture approach, taking into consideration an environment that supports the recovery process of the victims. The aim of this design is to create a safe, comfortable, and supportive environment for the physical and psychological recovery of the victims. The safe house is designed with a concept that focuses on spatial layout, the selection of soothing colours, appropriate lighting arrangements, and the use of natural elements such as plants and water to create an environment that supports the healing process. Additionally, the safe house is equipped with facilities that support recovery activities, such as counselling rooms, play areas, communal spaces, and living quarters. It is hoped that this safe house will serve as a place of protection for female and child victims of violence, where they can receive support, guidance, and comprehensive recovery. The safe house is expected to provide a real solution for addressing cases of violence and offer protection and opportunities for victims to start a better life anew.